2006
DOI: 10.1007/s10439-006-9216-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Breathing Pattern and Lung Size on the Alcohol Breath Test

Abstract: Highly soluble gases exchange primarily with the bronchial circulation through pulmonary airway tissue. Because of this airway exchange, the assumption that end-exhaled alcohol concentration (EEAC) is equal to alveolar alcohol concentration (AAC) cannot be true. During exhalation, breath alcohol concentration (BrAC) decreases due to uptake of ethanol by the airway tissue. It is therefore impossible to deliver alveolar gas to the mouth during a single exhalation without losing alcohol to the airway mucosa. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 12 publications
(23 reference statements)
2
30
0
Order By: Relevance
“…Heavy alcohol consumption, or abuse, increases morbidity among patients with community-acquired pneumonia. Others have suggested that both the delivery of ethanol to airways in the lungs during chronic alcohol abuse, and formation and accumulation of metabolites of ethanol may contribute to other lung and airway disorders, including asthma (Hlastala., 1998; Hlastala and Anderson, 2007; Siu et al , 2010; Kaphalia and Calhoun, 2013). Accordingly, the metabolic and immunologic effects of moderate consumption of alcohol are of considerable interest, both scientifically and clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy alcohol consumption, or abuse, increases morbidity among patients with community-acquired pneumonia. Others have suggested that both the delivery of ethanol to airways in the lungs during chronic alcohol abuse, and formation and accumulation of metabolites of ethanol may contribute to other lung and airway disorders, including asthma (Hlastala., 1998; Hlastala and Anderson, 2007; Siu et al , 2010; Kaphalia and Calhoun, 2013). Accordingly, the metabolic and immunologic effects of moderate consumption of alcohol are of considerable interest, both scientifically and clinically.…”
Section: Introductionmentioning
confidence: 99%
“…From our recent investigations, gases that are highly soluble in both blood and water (λ w =λ b >100 like acetone) exchange primarily in the airways (Fig 2A). The mechanism of this exchange has been described for elimination of soluble gases from the body 1,3,4,18,23 . Fresh inhaled air absorbs inert gas from the airway mucus, depletes the concentration of soluble gas in the mucous layer, and becomes fully saturated with highly soluble gas before reaching the alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to bias against people with smaller lung size. 9 We postulated that patients with significant chest injuries would not be able activate the breath analysis device due to pain and compromised respiratory function. In testing this hypothesis on patients undergoing thoracic surgical procedures, we chose the 2 nd postoperative day because they were on patient-controlled morphine analgesia rather than epidural or intrathecal morphine, which are not comparable to the morphine analgesia provided by pre-hospital care practitioners or accident and emergency departments.…”
Section: Discussionmentioning
confidence: 99%